Design of a Smart Model For Geolocation and E-commerce in the Semantic Web - Bennani, Anas; Khoulji, Samira; Larbi, Kerkeb Moamed (Transactions on Engineering and Computing Sciences, 2017)
Currently, e-commerce has become a pillar of the economy; there are huge growths of websites that offer different products to sell.This variety of web portals and products requires intelligent and autonomous operation to successfully the buying / selling process.The semantic web which is an initiation of the inventor of the web Tim Berners-lee proposes advanced technical solutions that act on the organization and the structuration of the data through ontologies. In this article we will discuss the subject of e-commerce in company with the area of geolocation. This document proposes a new solution allowing taking advantage of the geographical location of a customer to be located in relation to the stores that surround it.